Hodological patterning as an organizing principle in vertebrate motor circuitry - Glover, Joel C. (Frontiers in Neuroanatomy, 2025)
Hodological patterning refers to developmental mechanisms that link the location of neurons in the brain or spinal cord to specific axonal trajectories that direct connectivity to synaptic targets either within the central nervous system or in the periphery. In vertebrate motor circuits, hodological patterning has been demonstrated at different levels, from the final motor output of somatic and preganglionic autonomic neurons targeting peripheral motoneurons and ganglion cells, to premotor inputs from spinal and brainstem neuron populations targeting the somatic motoneurons and preganglionic autonomic neurons, to cortical neurons that delegate movement commands to the brainstem and spinal neurons. In many cases molecular profiling reveals potential underlying mechanisms whereby selective gene expression creates the link between location and axon trajectory. At the cortical level, somatotopic organization suggests a potential underlying hodological patterning, but this has not been proven. This review describes examples of hodological patterning in motor circuits and covers current knowledge about how this patterning arises.